1992
DOI: 10.1007/bf03348735
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting acromegaly and a unilateral cortisol-producing adrenal adenoma: a possible variant of multiple endocrine neoplasia type I

Abstract: An unusual case of coexisting acromegaly and Cushing's syndrome is reported in a 34-yr-old female. There was no biochemical or morphological evidence to suggest the presence of other endocrinopathies. She did not have any family history to suggest a hereditary tendency to endocrine disorders. Her acromegaly and Cushing's syndrome were proven to be due to a pituitary somatotroph adenoma and a cortisol-producing adenoma in the right adrenocortex, respectively. Surgical removal of both tumors led to a marked bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Subsequently, the authors followed nine of the 27 patients for one year and identified one patient with subclinical hypercortisolism who exhibited an increase in the size of the adrenal mass, similar to that noted in our case (8,9). To our knowledge, other than the above-mentioned case reported by Scaroni et al and our current case, only three cases of acromegaly accompanied by adrenocorticotropic hormone-independent subclinical Cushing's syndrome have been reported (10)(11)(12). No other forms of endocrinological neoplasia were observed in any of the previously reported four cases.…”
Section: Discussionsupporting
confidence: 82%
“…Subsequently, the authors followed nine of the 27 patients for one year and identified one patient with subclinical hypercortisolism who exhibited an increase in the size of the adrenal mass, similar to that noted in our case (8,9). To our knowledge, other than the above-mentioned case reported by Scaroni et al and our current case, only three cases of acromegaly accompanied by adrenocorticotropic hormone-independent subclinical Cushing's syndrome have been reported (10)(11)(12). No other forms of endocrinological neoplasia were observed in any of the previously reported four cases.…”
Section: Discussionsupporting
confidence: 82%
“…A recent review of the English literature revealed that there were only two reports of the coexistence of acromegaly and ACTHindependent Cushing's syndrome. One was a case of acromegaly with Cushing's syndrome due to bilateral nodular adrenocortical hyperplasia [16], and the other was due to a unilateral adrenocortical adenoma [17]. The latter case, which had been previously reported by us, was a case of preclinical Cushing's syndrome [17].…”
Section: Discussionmentioning
confidence: 99%
“…One was a case of acromegaly with Cushing's syndrome due to bilateral nodular adrenocortical hyperplasia [16], and the other was due to a unilateral adrenocortical adenoma [17]. The latter case, which had been previously reported by us, was a case of preclinical Cushing's syndrome [17]. After adrenalectomy, patients with overt Cushing's syndrome usually suffer from adrenal insufficiency requiring glucocorticoid replacement therapy for 9-33 months [13], but in our patient, glucocorticoid replacement therapy could be withdrawn as early as 8 weeks after adrenalectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The second patient was not diabetic before left adrenalectomy (7). Reports on the other three patients with acromegaly and Cushing's syndrome did not mention the glucose control status (8,9,11).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 5 such cases have been reported in the literature (7)(8)(9)(10)(11). We herein describe a 56-year-old woman with both acromegaly and a unilateral cortisol-producing adrenal adenoma who showed a dramatic improvement in glucose control following the treatment of her acromegaly and Cushing's syndrome.…”
Section: Introductionmentioning
confidence: 92%